The Official and Unofficial Markets for Sterling - Harris, S. E. (Quarterly Journal of Economics, 1940)
The Official and Unofficial Markets for Sterling Get access S. E. Harris S. E. Harris Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 4_Part_1, August 1940, Pages 655–664, https://doi.org/10.1093/qje/54.4_Part_1.655 Published: 01 August 1940